2009
DOI: 10.1016/j.fcr.2009.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate global sensitivity analysis for dynamic crop models

Abstract: Dynamic crop models are frequently used in ecology, agronomy and environmental sciences for simulating crop and environmental variables at a discrete time step. They often include a large number of parameters whose values are uncertain, and it is often impossible to estimate all these parameters accurately. A common practice consists in selecting a subset of parameters by global sensitivity analysis, estimating the selected parameters from data, and setting the others to some nominal values. For a discrete-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(94 citation statements)
references
References 95 publications
(141 reference statements)
1
90
0
3
Order By: Relevance
“…To date, no formal sensitivity analyses have been performed on perennials grown for biofuel and most sensitivity analyses performed for annual crops have mainly focused on aboveground growth parameters [35,52]. This study investigates 45 parameters relevant to growth and nutrients cycling of switchgrass to analyze the impact from both above and belowground parameters for perennial grass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, no formal sensitivity analyses have been performed on perennials grown for biofuel and most sensitivity analyses performed for annual crops have mainly focused on aboveground growth parameters [35,52]. This study investigates 45 parameters relevant to growth and nutrients cycling of switchgrass to analyze the impact from both above and belowground parameters for perennial grass.…”
Section: Discussionmentioning
confidence: 99%
“…However, caution should be taken when simplifying the complex structure of crop models because some model parameters may have little effect on certain response variables, but they may play key roles in other processes [65]. Additionally, the dynamic characteristics of parameter sensitivity need to be considered because parameter sensitivity may evolve over time [35]. The ":" denotes an interaction between two parameters a The definitions and the ranges of these identified parameters are listed in Table 1 b The response range is (the minimum value, the maximum value) under the interaction for each response variable c The percentage change was calculated as the difference between the maximum and the minimum value divided by the minimum d Average is the averaged percentage change across all the interactions for CROP and PARM, respectively…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since PCE reduces the computational expense of uncertainty propagation, it has been widely applied in complex environmental problems including water quality modeling (Moreau et al 2013), large scale socio-hydrologic modeling coupled with Agent-Based Models (Hu et al 2015), groundwater hydrogeological modeling (Deman et al 2016) and in other dynamic modeling examples such as crop modeling (Lamboni et al 2009) and seawater intrusion (Rajabi et al 2015). Moreover, an extensive review of basic principles and applications of PCE in computational fluid dynamics was conducted by Najm (2009).…”
Section: Sleuth For Urban Growth and Land-use Change Modelingmentioning
confidence: 99%
“…Considering high parameter correlation in models, recently developed multivariate and global sensitivity analyses allow the simultaneous testing of multiple parameter changes and can analyze direct and indirect effects of each parameter, the advantages of which are well illustrated in the sensitivity analysis of crop model parameters [67,68]. Considering that previous sensitivity analyses were only concerned with the effect on the final output results, it has been recently suggested that it is necessary to perform a multivariate time series of the sensitivity analysis for the daily output of the results obtained from a discontinuous-step simulation model [69], and it is important to reduce the uncertainty in the model parameter estimation. It is noted that, if we consider the model structure of uncertainty based on a single model of sensitivity analysis, possible errors in the model structure of uncertainty will propagate to the assessment of parameter uncertainty [70].…”
Section: Sensitivity Analysismentioning
confidence: 99%